Influences of Biopetrol-Ethanol Fuel on Performance and Emission in Internal Combustion Engine - Jaat, Norrizam; Tukijan, Johari; Mat Nawi, Nazuandie; Khalid, Amir; Sapit, Azwan; Mohd, Sofian (Journal of Automotive Powertrain and Transportation Technology, 2022)
The purpose of this study is to experimentally investigate the engine performance and pollutant emission of a commercial SI engine using ethanol–gasoline blended fuels with various blended rates (0%, 5%, 10%, 20%, and 30%). Fuel properties of ethanol–gasoline blended fuels were first examined by the standard ASTM methods. Results showed that by increasing the ethanol content, the heating value of the blended fuels is decreased, while the octane number of the blended fuels increases. It was also found that with the increment of ethanol content, the Reid vapor pressure of the blended fuels initially increases to a maximum at 10% ethanol addition, and then decreases. Results of the engine test indicated that using ethanol–gasoline blended fuels, torque output and fuel consumption of the engine slightly increase; CO and HC emissions decrease dramatically as a result of the leaning effect caused by the ethanol addition; and CO2 emission increases because of the improved combustion. Finally, it was noted that NOx emission depends on the engine operating condition rather than the ethanol content.